HUBUNGAN TINGKAT PENGETAHUAN TENTANG KESEHATAN REPRODUKSI DENGAN PERILAKU SEKSUAL BERISIKO PADA REMAJA DI SMK NEGERI 1 KUTALIMBARU - sitepu, Jujuren br (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2015)
Everyone has experienced to be adolescence. At this period, it will experience achange process bothbiological and psychological. The change influenced by society, close friend and mass media. The level ofthis research is an level of result, related to physical prosperity, bouncing and contact social, not only facefrom disease or weakness in all matter of related to health reproduce, function and its process. Adolescentattitude in this research is an attitude which is done to avoid the sexual contagion. It is a disease which isresulted by free sexual that happened of adolescent. Therefore, sex education to adolescent how to take carethe reproduction organ to be healthy. Venereal diseases have been recognized, but after found a new diseasethe term changed to be sexual of transmitted Disease (STD) or sexual sectional. This research is analyticdescriptive with a cross sectional research. It means that the data are taken at the same time. This researchis done on October 2013 in SMUN 1 Kutalimbaru . The population is student of class ,11,12,13 SMUN 1Kutalimbaru amount 257 samples. The conclusion from this research is the result of this research iscounted by 68 % adolescent categorized as sex active, there is no relation meaning between levels ofreproduction health of knowledge with the sexual contagion. From the statistical test with the level ofmistake is a 5 % (0,05) and P value is 0,673, so Ho is refused there is no relation meaning betweenadolescent attitudes with the sexual contagion, from the statistical test with the level of mistake is a 5 %(0,05)and P value is 1000, so Ho is refused.